2021
DOI: 10.3389/fmed.2021.640416
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Sleep Disorder: A Review

Abstract: Patients in the perioperative period usually present with different types and degrees of sleep disorders, which can severely affect their post-operative outcomes. Multiple risk factors may lead to the occurrence of perioperative sleep disorders, including personal factors, psychological factors, surgery factors, and environmental factors. In this review, we summarize the potential risk factors for perioperative sleep disorders during hospitalization. And it also provides an overview of perioperative outcomes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 96 publications
(113 reference statements)
2
17
0
1
Order By: Relevance
“…Risk factors of CPSP are diverse, including acute postsurgical pain, genetic susceptibility, preceding pain, age, sex, and psychosocial factors (e.g., perioperative sleep disorder, fear, and anxiety) [ 5 ]. Recent research has highlighted the negative influence of perioperative sleep deprivation (SD) on CPSP [ 6 ]. SD significantly causes hyperalgesia, and it further enhances pain facilitation [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Risk factors of CPSP are diverse, including acute postsurgical pain, genetic susceptibility, preceding pain, age, sex, and psychosocial factors (e.g., perioperative sleep disorder, fear, and anxiety) [ 5 ]. Recent research has highlighted the negative influence of perioperative sleep deprivation (SD) on CPSP [ 6 ]. SD significantly causes hyperalgesia, and it further enhances pain facilitation [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among currently used scales for assessing sleep quality, like the PSQI questionnaire, Insomnia Severity Index, Athens Insomnia Scale, Epworth Sleepiness Scale, and General Sleep Disturbance Scale, the most commonly used assessment is PSQI on account of high reliability and validity[ 22 ]. The PSQI contains 19 self-rated questions and 5 questions rated by the bed partner or roommate.…”
Section: Discussionmentioning
confidence: 99%
“…It is hypothesized that there are 10 variables related to postoperative sleep disturbance, and the required positive sample size is 100. Previous studies reported that the incidence of postoperative sleep disorders is 49.7%, and is even up to 95% in cardiac surgery [ 30 , 31 ]. We assume that if the incidence of sleep disorders is 60%, then 167 patients are required.…”
Section: Methodsmentioning
confidence: 99%